Whitmore disease presenting as parotid abscess in a child - Xuan, Ngo Minh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Whitmore disease, alsocalled melioidosis, is an emerging infection in Vietnam after the heavy flood in 2020 with increasing case reports, mostly in adults but also in children. We report a child with parotid abscess, which is one of the common clinical manifestations in the paediatric population in Vietnam. He was previously healthy. The child recovered completely after surgical drainage and antibiotic treatment according to standard guidelines. Because the spectrum of disease in childhood is different from that in adults and underlying predisposing factors are usually not seen in children, a high index of suspicion is required for the diagnosis of paediatric melioidosis. Raising awareness among paediatricians in Vietnam of the clinical presentations of melioidosis in childhood is a prerequisite for improved ascertainment. The key role of the microbiology laboratory in the diagnosis of melioidosis is highlighted. Keywords: Melioidosis, Burkholderia pseudomallei, Parotid abscess, Children